A polyphasic approach to characterise two novel species of Phoma (Didymellaceae) from China - Chen, Qian; Zhang, Ke; Zhang, Guozhen; Cai, Lei (Phytotaxa, 2015)
Phoma odoratissimi sp. nov. on Viburnum odoratissimum and Syringa oblate, and Phoma segeticola sp. nov. on Cirsium segetum from China are introduced and described, employing a polyphasic approach characterising morphological characteristics, host association and phylogeny. Both species are the first records of Phoma species on their respective hosts. Multi-locus phylogenetic tree was inferred using combined sequences of the internal transcribed spacer regions 1 & 2 and 5.8S nrDNA (ITS), and partial large subunit 28S nrDNA region (LSU), β-tubulin (TUB) region and RNA polymerase II (RPB2) region. The two new species clustered in two separate and distinct lineages, and are distinct from their allied species.